Effectiveness in protected areas at resisting development pressures in China. (April 2022) - Meng, Ziqi; Dong, Jinwei; Zhai, Jun; Huang, Lin; Liu, Min; Ellis, Erle C.
Abstract: Protected areas (PAs) are designed to conserve biodiversity and protect the species within their boundaries. However, some PAs are not achieving these goals, partly due to human activities inside and outside PAs. Here we evaluated the ability of 290 national-level PAs in China to reduce the impacts of economic development pressures using remote sensing-based fine resolution impervious surface area (ISA) and nighttime light (NTL) data as proxies of development pressure. We measured and compared the development pressure in protected areas and within buffers the same size in the area of the PAs (namely outside of the PAs). We also investigated whether the performance of PAs will be threatened by outside development pressure. According to the ISA, we found that 176 of the PAs had more development pressure outside their boundaries than inside PAs in 2018. For 175 PAs, we found a higher increasing rate of impervious areas outside of the PAs from 2000 to 2018, which suggested that increased human activities outside of the PAs were placing increased development pressure on the PAs. The PAs with higher development pressure outside their boundaries were more common in populous regions, especially in eastern China. Consistent with our findings from the ISA data, the NTL data also indicated that national PAs in China have faced increasing development pressures from outside PAs from 2000 to 2018. Our study warns that more attention should be paid to economic development pressures from the areas surrounding PAs to sustain their biodiversity protection over the long run. Highlights: More development pressure in outside PAs than inside national PAs in China in 2018. Higher growth of development pressure in outside PAs than inside during 2000–2018. Outside of the PAs were placing increased development pressure on the PAs. PAs with higher development pressure were more common in populous regions. More attention should be paid to development pressure from areas surrounding PAs.